Total synthesis of (+)-isolaurepan - Tripathi, Divya; Kumar, Pradeep (Tetrahedron Letters, 2008)
A versatile and efficient method for the enantioselective synthesis of 2,7-cis-disubstituted oxepane 1c, (+)-isolaurepan, using oxidative resolution of a secondary alcohol and highly diastereoselective Et(3)SiH/TMSOTf-promoted reductive cyclization of a hydroxy ketone is described. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Cis-selective cyclization; Cyclic ethers; Isolaurepan; Oxepanes; Oxidative resolution of secondary alcohols

Transition metal catalysis-a unique road map in the stereoselective synthesis of 1,3-polyols - Kumar, Pradeep; Tripathi, Divya; Sharma, Brijesh M.; Dwivedi, Namrata (Organic & Biomolecular Chemistry, 2017)
The present review summarizes recent diverse reactions employed in the formation of 1,3-polyols providing an overview of the mechanistic pathway and the enantioselectivity obtained, in terms of the properties of transition metals directly involved in the catalytic transformations and their interaction with various ligands.